Inferring the phylogenetic position of Brugia pahangi using 18S ribosomal RNA (18S rRNA) gene sequence - Fong, M.Y.; Thanabalan, A.; Muslim, A.; Lau, Y.L.; Sivanandam, S.; Mahmud, R. (2008)
This paper presents the first reported use of 18S rRNA gene sequence to determine the phylogeny of Brugia pahangi. The 18S rRNA nucleotide sequence of a Malaysian B. pahangi isolate was obtained by PCR cloning and sequencing. The sequence was compared with 18S rRNA sequences of other nematodes, including those of some filarial nematodes. Multiple alignment and homology analysis suggest that B. pahangi is closely related to B. malayi and Wuchereria bancrofti. Phylogenetic trees constructed using Neighbour Joining, Minimum Evolution and Maximum Parsimony methods correctly grouped B. pahangi with other filarial nematodes, with closest relationship with B. malayi and W. bancrofti. The phylogeny of B. pahangi obtained in this study is in concordance with those previously reported, in which the 5S rRNA gene spacer region and cytochrome oxidase subunit I (COI) sequences were used.